THE INFLUENCE OF EARNING PER SHARE, PRICE TO BOOK VALUE, RETURN ON ASSET AND RETURN ON EQUITY TOWARD STOCK PRICE ON BASIC INDUSTRY AND CHEMICALS COMPANY LISTED IN INDONESIA STOCK EXCHANGE - Melina Melina; Frederick Emerio Tanny (Jurnal Penelitian Akuntansi (JPA), 2022)
Basic Industry and Chemicals or people referred as downstream business line generates a fundamental product, which is then utilized to other manufacture to produce. This research aims to determine the influences of Earning Per Share, Price to Book Value, Return on Asset, Return on Equity, toward stock price. The population in this research are all basic industry and chemicals companies listed in Indonesia Stock Exchange  .The technique of determining the sample using purposive sampling method and sample acquired from 32 companies for the year 2018 to 2020. This research contains five variables which are one dependent variable and four independent variables.This research is using quantitative approach and IBM SPSS Statistics ver. 27 software to display results of statistical analysis conducted in this research. Total sample of 96, to meet the requirements of the classical assumption test the final data used totaling 61.The analytical model used in this study is a multiple linear regression model. The results of this study indicate that EPS, PBV, and ROE have a significant influence on stock prices. However, ROA have an insignificant influence on stock prices. EPS, PBV, ROE, ROA simultaneously influence stock price. Keywords: Earning Per Share, Price to Book Value, Return on Asset, Return on Equity, Stock Price, Basic Industry